Transport and profile broadening in the private flux region of ASDEX upgrade and role for power exhaust - D. Brida; G. Grenfell; O. Grover; D. Silvagni; M. Faitsch; U. Stroth; the ASDEX Upgrade Team; the EUROfusion Tokamak Exploitation Team (Nuclear Fusion)
Understanding the transport processes that determine the plasma profile widths in the scrape-off layer (SOL) and divertor region of tokamaks is crucial for successful power and particle exhaust management in future devices. Plasma transport from the SOL into the private flux region (PFR) broadens the profiles and could mitigate the power exhaust challenge. Analysis of ion current profiles, measured by Langmuir probes in the ASDEX upgrade (AUG) tokamak, shows that the ion current width in the PFR, normalized by the flux expansion between outer target and midplane, is about 1.2 mm in L-mode and 0.9 mm in inter-ELM H-mode plasmas. The measured widths agree within a factor of two with predictions from an analytical model, based on Pfirsch-Schlüter flows. According to the model, the ion PFR width increases with the distance Δ R between the outer target and X-point major radii, and scales inversely with the poloidal magnetic field $B_\mathrm p$ . For the tokamaks ITER and SPARC the model predicts PFR widths below 0.3 mm.